2021
DOI: 10.1029/2020ja028837
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for the In‐Situ Generation of Plasma Depletion Structures Over the Transition Region of Geomagnetic Low‐Mid Latitude

Abstract: On a geomagnetic quiet night of October 29, 2018, we captured an observational evidence of the onset of dark band structures within the field‐of‐view of an all‐sky airglow imager operating at 630.0 nm over a geomagnetic low‐mid latitude transition region, Hanle, Leh Ladakh. Simultaneous ionosonde observations over New Delhi shows the occurrence of spread‐F in the ionograms. Additionally, virtual and peak height indicate vertical upliftment in the F layer altitude and reduction in the ionospheric peak frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…During 5 years of airglow observations from a mid-latitude station, Hanle (32.7°N, 78.9°E; Mlat. 24.1°N), Ladakh, India, different types of plasma structures, viz., electrified and non-electrified medium-scale traveling ionospheric disturbances (MSTIDs), mid-latitude spread-F (MSF), and mid-latitude field-aligned plasma depletion, have been observed in 630.0 nm images (Patgiri, Rathi, Yadav, Sarkhel, et al, 2024;Rathi et al, 2021Rathi et al, , 2022Rathi et al, , 2024Sivakandan et al, 2020Sivakandan et al, , 2021Yadav, Rathi, Gaur, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…During 5 years of airglow observations from a mid-latitude station, Hanle (32.7°N, 78.9°E; Mlat. 24.1°N), Ladakh, India, different types of plasma structures, viz., electrified and non-electrified medium-scale traveling ionospheric disturbances (MSTIDs), mid-latitude spread-F (MSF), and mid-latitude field-aligned plasma depletion, have been observed in 630.0 nm images (Patgiri, Rathi, Yadav, Sarkhel, et al, 2024;Rathi et al, 2021Rathi et al, , 2022Rathi et al, , 2024Sivakandan et al, 2020Sivakandan et al, , 2021Yadav, Rathi, Gaur, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…During 5 years of airglow observations from a mid‐latitude station, Hanle (32.7°N, 78.9°E; Mlat. 24.1°N), Ladakh, India, different types of plasma structures, viz., electrified and non‐electrified medium‐scale traveling ionospheric disturbances (MSTIDs), mid‐latitude spread‐F (MSF), and mid‐latitude field‐aligned plasma depletion, have been observed in 630.0 nm images (Patgiri, Rathi, Yadav, Sarkhel, et al., 2024; Rathi et al., 2021, 2022, 2024; Sivakandan et al., 2020, 2021; Yadav, Rathi, Sarkhel, et al., 2021; Yadav, Rathi, Gaur, et al., 2021). The present study reports a first of its kind event in which the same plasma‐depleted structure was observed both in 630.0 and 557.7 nm images on a geomagnetically quiet night (Ap = 3) on 26 June of low solar active year 2021.…”
Section: Introductionmentioning
confidence: 99%
“…Sivakandan et al. (2020, 2021) reported a rare case of midlatitude spread F with onset of a midlatitude plasma depletion structure within the field of view (FOV) of the imager. Rathi et al.…”
Section: Introductionmentioning
confidence: 99%
“…Within a short period of 3 years, several interesting events have been observed over this transition region. Sivakandan et al (2020Sivakandan et al ( , 2021 reported a rare case of midlatitude spread F with onset of a midlatitude plasma depletion structure within the field of view (FOV) of the imager. Rathi et al (2021) found simultaneous coexistence of periodic and single dark band MSTIDs.…”
mentioning
confidence: 99%